Digital Marketing Training For Tilapia Fish Farming Businesses In Bladu Kulon Village, Tegal Siwalan Subdistrict, Probolinggo Regency - Nuntupa; Zahida I’tisoma Billah; Ahmad Zainullah; Hawa’ Hidayatul Hikmiyah; Abd Ghafur (CENDEKIA: Jurnal Pengabdian Masyarakat, 2025)
Community service through the Kuliah Kerja Nyata (KKN) program in Blado Kulon Village, Tegal Siwalan District, Probolinggo Regency was carried out using the Asset-Based Community Development (ABCD) approach. This approach was chosen because it emphasizes the utilization of community assets, strengths, and local potential, particularly in the tilapia fish farming sector, which serves as the village’s main asset. Through the ABCD method and Appreciative Inquiry, the mentoring process was implemented in five key stages: discovery, dream, design, define, and destiny. This program focused on developing community capacity, especially among members of the Mina Mandiri tilapia farming group (POKDAKAN), in enhancing their knowledge and skills in digital marketing. The results of the program indicate positive changes within the community, particularly in business management, mindset, and the ability to utilize social media as a marketing platform. Training activities, including the creation of Shopee and Lazada accounts and the optimization of WhatsApp Business, contributed to increased creativity and independence in promoting tilapia farming products. These findings reinforce that the ABCD approach effectively fosters self-reliance, confidence, and empowerment within the community to develop its local potential. Overall, the digital marketing assistance program based on local assets proved effective in improving the capacity of the Blado Kulon Village community. This initiative is expected to serve as an initial step toward further business innovation development and strengthening the village economy through community-based assets.